Cognitively-Based Compassion Training (CBCT®) in Breast Cancer Survivors: A Randomized Clinical Trial Study. (September 2018) - Gonzalez-Hernandez, Edgar; Romero, Rocio; Campos, Daniel; Burychka, Diana; Diego-Pedro, Rebeca; Baños, Rosa; Negi, Lobsang Tenzin; Cebolla, Ausiàs
Context. Breast cancer (BC) requires a significant psychological adaptation once treatment is finished. There is growing evidence of how compassion training enhances psychological and physical well-being, however, there are very few studies analyzing the efficacy of compassion-based Interventions on BC survivors. Objective. To study the efficacy of the Cognitively-Based Compassion Training (CBCT) protocol in a BC survivor sample on quality of life, psychological well-being, fear of cancer recurrence, self-compassion, and compassion domains and mindfulness facets. Furthermore, enrollment, adherence, and satisfaction with the intervention were also analyzed. Methods. A randomized clinical trial was designed. Participants (n = 56) were randomly assigned to CBCT (n = 28) or a treatment-as-usual control group (TAU; n = 28). Pre-post intervention and 6-month follow-up measures took place to evaluate health-related quality of life, psychological well-being; psychological stress, coping strategies, and triggering cognitions; self-compassion and compassion; and mindfulness in both intervention and wait-list groups. Results. Accrual of eligible participants was high (77%), and the drop-out rate was 16%. Attendance to CBCT sessions was high and practice off sessions exceeded expectations). CBCT was effective in diminishing stress caused by FCR, fostering self-kindness and common humanity, and increasing overall self-compassion scores, mindful observation, and acting with awareness skillsets. Conclusion. CBCT could be considered a promising and potentially useful intervention to diminish stress caused by FCR and enhance self-kindness, common humanity, overall self-compassion, mindful observation, and acting with awareness skillsets. Nevertheless, future randomized trials are needed and a process of deeper cultural adaptation required.